Strategi Pemberdayaan UMKM Pasca-Pandemi oleh Dinas Koperasi, Usaha Kecil dan Menengah Provinsi Kepulauan Bangka Belitung - Hidayatullah, Muhammad Rifqi (Journal of Politics and Democracy, 2024)
This study analyzes the empowerment strategies for Micro, Small, and Medium Enterprises (MSMEs) implemented by the Office of Cooperatives, Small and Medium Enterprises (OCSME) of Bangka Belitung Province as part of the National Economic Recovery program in the post-COVID-19 period. Employing a descriptive qualitative approach through interviews, observations, and documentation, this research examines the stages of planning, implementation, and evaluation of empowerment programs while identifying supporting and inhibiting factors. The findings reveal that OCSME’s empowerment strategies have had positive impacts in terms of enhancing MSME capacity and improving the regional economy, although challenges remain in program sustainability, low human resource quality, and limited access to financing. Analysis using Jim Ife’s empowerment framework demonstrates that OCSME’s strategies encompass structural dimensions through the formulation of strategic plans (Renstra), economic dimensions through the provision of business legality and market access, and community capacity building through the Integrated Business Service Center (PLUT). This study highlights the importance of cross-sectoral synergy and institutional capacity strengthening in creating a competitive, inclusive, and sustainable MSME ecosystem.